Digital Teaching Material Transformation: Design Student Worksheets using GeoGebra Based on Local Wisdom by Pre-service Teachers - Sugiarni, Rani; Jusniani, Nia; Rodríguez-Nieto, Camilo Andrés (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
The limited ability of teachers to design interesting digital mathematics teaching materials, as well as the context that is free from local participant wisdom, also causes misconceptions and difficulties in understanding mathematical concepts in depth for students. This study aims to analyze the ability of pre-service mathematics teachers to design student worksheets using the GeoGebra application based on local wisdom in mathematics learning. This study uses a qualitative method with a descriptive analytical approach to describe the ability of the pre-service mathematics study program to design student worksheets with Geogebra software based on local wisdom in mathematics learning. Participants in this study were in the pre-service mathematics education study program in West Java. The data collection technique used documentation in the form of student digital open material designs. The digital teaching materials designed by pre-service mathematics students are worksheets with GeoGebra software based on local wisdom. The research instruments were lecturer and teacher assessment sheets to ensure the feasibility of digital teaching materials and student response questionnaires for the practicality of the results of the digital teaching material plan used by students. The results of the study can be explained by the fact that the ability of students in the mathematics education study program to create digital open materials, namely student worksheets and GeoGebra software media, is worthy of the high category as assessed by lecturers and teachers. Meanwhile, the students' response to the socialization of digital open media design by students gave a positive response with a high category. Thus, students' digital teaching materials support meaningful mathematics learning for students with technology and local wisdom.